ANALISIS PENDAPATAN DAN SISTEM PEMASARAN SUSU KAMBING DI DESA SUNGAI LANGKA KECAMATAN GEDUNG TATAAN KABUPATEN PESAWARAN - Riza Arviansyah; Sudarma Widjaya; Suriaty Situmorang (Lampung University, 2015)
The objective of this research were to : (1) identify goat’s milk production and income, and (2) analyze marketing system efficiency of goat’s milk. Location of this research was in Sungai Langka Village Gedung Tataan District Pesawaran Regency was purposively selected, 37 breeders and 3 broker as marketing agency for the sample. Sampling method for breeders used census method, while sampling method for marketing agency used snowball method. Data are drawn in July-December 2014. This research used descriptive qualitative and quantitative for the data analysis. The results of this research showed that : (1) average of production for goat’s milk in location’s research is still below the potential. Income is already profitable, and (2) marketing system of goat’s milk in location’s research was inefficient. Key words : goat’s milk, income, marketing, production